Generating Ecotrust: A Relational Response to the Infodemic. (November 2021) - Hirschmann, Krista; Isgro, Kirsten
Trust has been studied by a variety of disciplines and perspectives, with many pointing towards the need for a more complex and dynamic approach to understanding trust as a relational process. This paper introduces the concept of ecotrust within healthcare as means to capture a co-produced, relational response to the abundance of (mis)information produced by the current infodemic. As an approach that recognizes the contributions of and impact on all members of the system, ecotrust encourages research that explores the process by which trust emerges as a shared reality from both the provider's or healthcare team's perspectives, as well as the patient experience, potentially leading to new conversations and strategies for partnering together. Finally, ecotrust encourages the skills of relationship-centered communication as a specific strategy for entering conversations with curiosity and empathy, thus encouraging relationship-building as a humanistic first step for responding to (mis)information.